The role of CEO relative standing in acquisition behavior and CEO pay - Seo, Jeongil; Gamache, Daniel L.; Devers, Cynthia E.; Carpenter, Mason A. (Strategic Management Journal, 2015)
In this study, we develop and test a theory of CEO relative pay standing. Specifically, we propose that CEO s with negative relative pay standing status (underpaid relative to comparison CEO s) will engage in acquisition activity, as a self‐interested means of attempting to realign their pay with that of their peers. We further propose that, when CEO s with negative relative pay standing acquire, they will tend to finance those acquisitions more heavily with stock than cash, to mitigate the risk associated with those deals. Finally, we argue that acquisition activity will partially mediate the influence of CEO negative relative pay standing on subsequent CEO compensation increases; however, that pay growth will come primarily in the form of long‐term incentive pay. Our results support our predictions . Copyright © 2014 John Wiley & Sons, Ltd.